THE VALIDITY AND PRACTICALITY OF THE POPULAR SCIENTIFIC BOOK "DIVERSITY OF HALIAU RIVER FISH" AGAINST STUDENTS' CRITICAL THINKING SKILLS - Putri, Rezna Kartika; Dharmono, Dharmono; Zaini, Muhammad (Journal of Banua Science Education, 2024)
Learning resources are one component of learning that is quite important to determine the success or failure of learning. This development research aims to obtain the validity and practicality of popular scientific books Haliau river fish diversity in developing students ' critical thinking skills. The development research was carried out through formative evaluation of the Tessmer model. The research was carried out for six months at the faculty of education, department of biology. The research subjects in the expert review consisted of 3 lecturers of the ULM biology masters education, one to one consisted of 3 students, the small test consisted of 5 students and the field test consisted of 10 students who participated in the vertebrate zoology course. The research data was measured by calculating the validity and practicality scores and analyzed descriptively. Product validation aspects are coherence, legibility, vocabulary, active and passive sentences, applications and implications, definitions and explanations and other styles of devices. Meanwhile, the practicality data was obtained from the students' readability test data and student responses. The results showed that the validity based on the results of the expert team's validation had an average score of 88, 46 % with a very valid category. While the practicality based on the results of student responses with a percentage of 94.56%, classified as very good criteria and the implementation of popular scientific books at 88.89 % with very good criteria. Thus BIP can already be used in learning vertebrate zoology courses.